Disaster from water pollution in Indonesia: Unsustainable human interaction with the environment and its social impacts - Ardinata, Rendri; Manurung, Widya Motivasi (ASEAN Natural Disaster Mitigation and Education Journal, 2025)
Background: Water is a vital global resource, available in forms such as surface water and groundwater. Human activities, particularly increased population, have led to unsustainable water use, causing pollution in rivers, lakes, and oceans. In Indonesia, water resources, including in Muara Teluk Jakarta, are polluted by organic, inorganic, chemical, and plastic pollutants, especially microplastics and debris. Method: This study uses a qualitative approach with secondary data from journals and water quality reports by DKI Jakarta Environmental Agency. The research involves classifying topics, analyzing human-environment interactions, and reviewing water quality data to assess pollution levels using the water quality index (WQI). The findings aim to inform effective water treatment strategies and policies for addressing water pollution in Indonesia. Findings: The study and data analysis of sea water quality of Muara Teluk Jakarta index trends from 2017-2023 show that conditions fluctuated in the 2017-2023 range but heavily polluted condition. These water pollution problems need appropriate and proper management to reduce pollutes and increase water quality from biological, chemical, or physical properties.  Well water management with customized condition will be very effective as one of solution for clean water supply and solution for sustainable water management in Indonesia. Conclusion: Effective water management strategies tailored to specific local conditions are essential to mitigate pollution and improve water quality in Indonesia. Sustainable water management is crucial for ensuring clean water supplies. Novelty/Originality of this article: This study highlights the persistent water pollution in Muara Teluk Jakarta, particularly from plastic and chemical contaminants, and the need for technological solutions to address water quality issues. It offers a practical approach to sustainable water management by exploring innovative methods to reduce pollution and improve water quality in Indonesia.